Hollow porous molecularly imprinted polymer for xylose detection in sugarcane bagasse by dispersive solid-phase extraction - Moriya, Diogo Hideki [UNESP]; de Souza Teles, Cláudio Fernando [UNESP]; dos Santos, Paula Mantovani [UNESP]; Wong, Ademar [UNESP]; Sotomayor, Maria D. P. T. [UNESP] (Royal Society of Chemistry (RSC), 2025)
Hollow porous MIP selectively extracted d -xylose with >98% recovery from sugarcane bagasse via DSPE. The adsorption capacity was 23.86 mg kg −1 , more than double that of conventional MIPs. The increasing generation of agro-industrial waste in Brazil presents an opportunity for the recovery of high value-added compounds. Xylose, a pentose derived from the hydrolysis of xylan, has several industrial applications, such as in the production of xylitol and furfural. In this study, a new xylose-selective hollow porous molecularly imprinted polymer (HMIP) was developed and applied to sugarcane samples via dispersive solid phase extraction (DSPE). The interaction occurred between the functional monomer and the template (xylose), followed by polymerization and subsequent removal of the template, creating selective cavities. The use of functionalized silica (SiO 2 –CC) as a core allowed the formation of hollow and porous structures, improving mass transfer and adsorption efficiency. The results indicated that the HMIP presented a maximum adsorption capacity of 22.99 mg g −1 , more than twice the capacity recorded for conventional MIPs. The polymer demonstrated high selectivity for xylose compared to other monosaccharides (glucose, arabinose, fructose, and sucrose), in addition to an adsorption efficiency of 83.80% in real samples of sugarcane bagasse hemicellulosic hydrolysate. In the solid phase removal (SPE) application, the HMIP reached 98.75% adsorption and maintained a high recovery rate after three reuse cycles (>93%). The results demonstrate the potential of the HMIP for the selective separation of xylose, contributing to the valorization of agro-industrial waste and promoting safe practices aligned with the principles of the circular economy and SDG 12 (responsible consumption and production).